Cerebral blood flow is modulated by astrocytic cAMP elevation independently of IP 3 R2-mediated Ca 2+ signaling in mice - Marta Vittani; Rasmus Herlo; Xiaowen Wang; Michala Daniela Bach Christensen; Camilla Trang Vo; Tsuneko Mishima; Peter Kusk; Ayumu Konno; Hirokazu Hirai; Takashi Tsuboi; Tetsuya Kitaguchi; Celia Kjaerby; et al. (Proceedings of the National Academy of Sciences, 2025)
Local neural activation drives regional increase of cerebral blood flow (CBF), in a phenomenon known as functional hyperemia. Astrocytes, which enwrap cerebral blood vessels and respond to neuronal activity through their G protein–coupled receptors (GPCRs), play a vital role in brain energy metabolism. Although astrocytic calcium (Ca 2+ ) signaling has been widely studied in relation to neurovascular coupling, the role of cyclic adenosine monophosphate (cAMP), another key second messenger of GPCRs, on CBF has not been established. In this study, we explored the effects of optogenetically induced astrocytic cAMP elevation on CBF. We engineered adeno-associated viral vectors (AAVs) to express a bacterial photoactivated adenylyl cyclase in astrocytes, which triggers an increase in cAMP upon blue light stimulation. Opto-stimulation also elevated astrocytic Ca 2+ , albeit with a delayed onset under mild stimulation. In vivo imaging of anesthetized and awake wild-type mice through a thinned skull preparation revealed that optogenetically induced astrocytic cAMP elevation led to pronounced arteriole dilation, with a latency of 1.8 s and maximal dilation reached within 10 s in the awake state and slower response under anesthesia. Mild opto-stimulation causing sensory-level cAMP elevations was sufficient to induce arteriole dilation. This effect was preserved in IP 3 receptor type 2-knockout (IP 3 R2 −/− ) mice, indicating a mechanism independent of GPCR-induced intracellular Ca 2+ elevations. These findings highlight astrocytic cAMP as a key modulator of cerebral vasodilation, contributing to our understanding of local CBF regulation. This study opens broad avenues for understanding astrocyte-mediated control of CBF and its implications in neurological diseases characterized by dysregulated blood flow.